Three new earthworm species of the tokioensis-group in the genus Amynthas (Oligochaeta: Megascolecidae) from Guangxi Province, China - Jiang, Ji-Bao; Dong, Yan; Yuan, Zhu; Qiu, Jiang-Ping (Zootaxa, 2018)
Three new species of the genus Amynthas are described from Guangxi Province, China. They are named A. dissimilis sp. nov., A. anteporus sp. nov. and A. marsupiformis sp. nov. All of them have two pairs of spermathecal pores in 6/7–7/8, and belong to the tokioensis-group. Their morphological characteristics are compared to similar species in tokioensis-group from China and other Asian countries. In addition, the mitochondrial COI and 12S-tRNA-Val-16S sequence of three new species were determined, then pairwise distances between species were calculated. Both morphological and molecular evidences could easily distinguish the new species from earthworms previously reported in the tokioensis-group.